Ethnography and nursing: an experience of the masters degree in nursing – UFC - Maria Grasiela Teixeira Barroso; Luiza Jane Eyre Xavier de Souza; Mirna Albuquerque Frota (Rev Rene)
It is about a research experience from graduating nursing students at a Public University of Ceará-Brazil that in their thesis or dissertations used the ethnography as methodology option. The aim was to identify if method adapted with the study object chosen. Was described the ethnographic method. The method was developed from the bibliographic research about cultural anthropology and ethnography. From the experience in use the ethnography method in their research, was analised the talks of the graduation students that was proved the importance of the ethnography for the investigation of different sociocultural context. It was concluded that the ethnographic study has contributed to enlarge the care perspective to the human being, respecting the transcultural aspect.